Mineral nutrition and specific leaf area of plants under contrasting long-term fire frequencies: a case study in a mesic savanna in Australia - de Souza, Marcelo Claro [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Cook, Garry David; Fujinuma, Ryosuke; Menzies, Neal William; Morellato, Leonor Patrícia Cerdeira [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2016)
Key message: The association between frequent long-term fires and soil fertility may control the nutritional status and leaf scleromorphism of Australian savanna species. Abstract: Fire frequency is considered to be a controlling factor for the structure of savanna vegetation, also affecting functional aspects of plants, yet studies contrasting long-term burnt and unburnt sites within the same area are rare. At fire-protected sites, one may expect to find woody vegetation with non-sclerophyllous leaves exhibiting a high nutrient concentration and growing on soils of high fertility. Using a burnt (14 times within the last 20 years) and an unburnt site (over the same period) within the same area of a mesic Australian savanna, we compared the soil fertility, specific leaf area (SLA) and leaf macronutrient concentration of the exclusive (species that occur at a single site), common (species that occur at both sites) and total (exclusive and common species combined) sampled tree species from the two sites. The exclusive, common and total sampled tree species had a lower SLA when growing at the burnt site than at the unburnt site. Soil from the burnt site was less fertile than the soil from the unburnt site, and the plants from the burnt site exhibited lower leaf nutrient concentrations when compared with those from the unburnt site. The association between fire and soil fertility was consistent with the differences in leaf scleromorphism between the sites under contrasting fire frequencies.
Keywords: Fire management; Leaf scleromorphism; Native plant nutrition; Soil fertility